Effect of Strain-Induced Precipitation on the Austenite Non-recrystallization (Tnr) Behavior of a High Niobium Microalloyed Steel - Rajinikanth, V.; Kumar, Tipu; Mahato, B.; Ghosh Chowdhury, Sandip; Sangal, Sandeep (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2019)
The non-recrystallization temperature ( T nr ) of high niobium microalloyed steel was determined from both multihit and double-hit compression tests obtained under plane strain condition. The T nr was determined to be in the range of 985 °C to 1010 °C for multihit conditions. The double-hit tests carried out at an interpass time of 5 seconds gave very low T nr in the range of 860 °C to 900 °C. In order to understand this, double-hit experiments were carried out for different interpass times (2, 15, 100 seconds) at three different temperatures (950 °C, 1050 °C, and 1150 °C). The negative softening behavior was observed at 950 °C for higher interpass times of 15 and 100 seconds. This implies that the T nr of this steel is well above 950 °C. This was due to the high amount of strain-induced precipitation of niobium carbonitrides at higher interpass times as revealed from TEM investigation. The precipitate size evolution considering the Dutta and Sellars nucleation condition in TC-PRISMA agrees well with the experimentally observed precipitate sizes. However, the evolution of Zener pinning forces considering TC-PRISMA nucleation condition is similar to both reported and experimentally determined values. The evolution of tensile properties also correlates well with the observed austenite recrystallization softening behavior. Therefore, a minimum interpass time of 15 seconds is required during double-hit compression tests to effectively precipitate Nb(C, N) and delay the static recrystallization softening behavior of this steel. This lead to the determination of comparable T nr values between double-hit and multihit methods.